A Effects of Media Exposure and My Trip My Adventure Impressions on Interest in Enhancing Nature Conservation - Nauval Illyasa; Siti Masitoh (Metakom, 2019)
Now days there have been many television shows which are documentation, travel, and trips that are broadcast by tv stations and much favored by the community especially young people like My Trip My Adventure is one of the educational programs whose purpose is to provide knowledge and invite the audience to learn more about preserving nature. In relation the researcher took the object of the Nature Lover Student (Mapala) member. The purpose of this study is whether there is an influence of exposure to television media and the My Trip My Adventure program simultaneously on the interest in improving nature conservation in the Mapala Community. The theory used by Uses and Gratification and Cultivation Theory. The research method used is a quantitative method. Data collection techniques were carried out using a questionnaire method. The results of this study partially had no effect on the media's exposure to the interest in preserving with t count 633 <t table 1,997 and the Sig. 0.528> 0.05, while Impressions My Trip My Adventure influences the interest in preserving t count 6,778> t table 1,975 and sig value 0,000 <0.05. This is concluded with the coefficient of determination showing the results of the influence of variables X1 (media exposure) and X2 (impressions) simultaneously on the Y variable (interest) of 54.5% and the remaining 45.5% is influenced by other factor.